Synergistic association of STX1A and VAMP2 with cryptogenic epilepsy in North Indian population. Issue 7 (14th June 2016) - Baghel, Ruchi; Grover, Sandeep; Kaur, Harpreet; Jajodia, Ajay; Parween, Shama; Sinha, Juhi; Srivastava, Ankit; Srivastava, Achal Kumar; Bala, Kiran; Chandna, Puneet; Kushwaha, Suman; Agarwal, Rachna; et al.
Abstract: Introduction: "Common epilepsies", merely explored for genetics are the most frequent, nonfamilial, sporadic cases in hospitals. Because of their much debated molecular pathology, there is a need to focus on other neuronal pathways including the existing ion channels. Methods: For this study, a total of 214 epilepsy cases of North Indian ethnicity comprising 59.81% generalized, 40.19% focal seizures, and based on epilepsy types, 17.29% idiopathic, 37.38% cryptogenic, and 45.33% symptomatic were enrolled. Additionally, 170 unrelated healthy individuals were also enrolled. Here, we hypothesize the involvement of epilepsy pathophysiology genes, that is, synaptic vesicle cycle, SVC genes (presynapse), ion channels and their functionally related genes (postsynapse). An interactive analysis was initially performed in SVC genes using multifactor dimensionality reduction (MDR). Further, in order to understand the influence of ion channels and their functionally related genes, their interaction analysis with SVC genes was also performed. Results: A significant interactive two‐locus model of STX1A _rs4363087| VAMP2 _rs2278637 (presynaptic genes) was observed among SVC variants in all epilepsy cases ( P 1000 ‐value = 0.054; CVC = 9/10; OR = 2.86, 95%CI = 1.88–4.35). Further, subgroup analysis revealed stronger interaction for the same model in cryptogenic epilepsy patients only ( P 1000 ‐value = 0.012; CVC = 10/10; OR = 4.59, 95%CI = 2.57–8.22). However, interactive analysis of presynaptic and postsynaptic genes did not show any significant association. Conclusions: Significant synergistic interaction of SVC genes revealed the possible functional relatedness of presynapse with pathophysiology of cryptogenic epilepsy. Further, to establish the clinical utility of the results, replication in a large and similar phenotypic group of patients is warranted. Abstract : We hypothesize the involvement of genetic variants from synaptic vesicle cycle (presynapse), ion channels and their functionally related genes (postsynapse) in pathophysiology of epilepsy. A highly significant interactive two‐locus model of STX1A_rs4363087|VAMP2_rs2278637 was observed in cryptogenic epilepsy (Corrected P = 0.012; CVC = 10/10; OR = 4.59, 95% CI = 2.57–8.22), thus revealing the possible functional relatedness of presynapse with pathophysiology of cryptogenic epilepsy.